Post-treatment late and long-term effects in bone sarcoma: A scoping review - Kaainat Khan; Kathleen Kane; Zoe Davison; Darrell Green (Journal of Bone Oncology)
Despite the fact that chemotherapy for bone sarcomas (e.g. Ewing sarcoma, osteosarcoma) has well-reported toxicities and that surgical intervention is frequently life altering, follow-up care to monitor for late and long-term effects beyond that of oncological surveillance in former patients is variable. Anecdotal evidence suggests that inconsistent follow-up means some former bone sarcoma patients are left to cope with post-treatment late and long-term effects with limited support. Here, we performed a scoping review to provide a more empirical identification of the knowledge gaps and to provide an overview of the peer reviewed academic literature reporting the late and long-term effects of treatment for bone sarcoma. JBI Scoping Review Network guidelines for charting, analysis and data extraction were followed. Literature searches were conducted in Medline (Ovid), Cochrane CENTRAL, EMBASE (Ovid), CINAHL, PsycINFO, Proquest and Web of Science (Clarivate Analytics) from March 2024 to September 2024. Paper titles and abstracts were screened by two independent reviewers followed by full text analysis by the lead researcher. Seventy-four peer reviewed articles were included in the analysis. Most studies were of a retrospective study design, some up to 20 years of follow-up and included chemotherapy, surgery and sometimes radiotherapy as the treatment modality. Our analysis identified secondary malignancies, cardio- and nephrotoxicity, lower bone mineral density and microarchitectural deterioration, cancer related fatigue and motor neuropathies as the major physical late and long-term effects requiring dedicated follow-up. In some cases, follow-up may need to span decades, especially given the increasing population of former patients. Our results form the evidence-based foundations for future work that might include late and long-term effect follow-up service mapping exercises and expanded clinical recommendations.